Renorrhaphy of Unilateral Grade V Blunt Renal Injury: Case Report - Achmad Romy Syahrial Rozidi; Budi Suwarno; Ogi Bahaurini Gumilar; Shaohong Lai (Biomolecular and Health Science Journal, 2022)
The kidney continues to be the most commonly injured organ in the genitourinary system, with the vast majority of cases being caused by blunt trauma. The majority of individuals with renal trauma are managed conservatively. However, hemodynamic instability, such as shock induced by renal hemorrhage or developing retroperitoneal hematoma (showing grade v renal trauma), renal pelvis or ureteral injury, as well as other renovascular pathologies, may signal the necessity for surgical intervention, which may include renorrhapy. Renorrhaphy in the setting of grade V renal trauma is very uncommon and has only been documented in a few cases in the preceding literature. We discuss a unique and complex case that was successfully managed, and we examine the relevant literature to give useful information for the management of blunt renal trauma patients.